Long-Term Evaluation of Wear and Retention in Magnet vs. Stud Attachments for Maxillary Implant-Retained Overdentures - Sumit Bhatt; Narahari Ranganatha; Sneha Kamasani; Shweta Singh; Dimple Bhawnani; Pratik Bumb (Journal of Pharmacy and Bioallied Sciences)
Background: Implant-retained overdentures are a reliable treatment modality for edentulous patients, offering enhanced function and esthetics. Magnet and stud attachments are commonly used for maxillary overdentures, but their long-term performance in terms of wear and retention requires further evaluation. Materials and Methods: This prospective clinical study included 40 edentulous patients rehabilitated with maxillary implant-retained overdentures. Patients were randomly divided into two groups: Group A (magnet attachments) and Group B (stud attachments), with 20 participants in each group. Retention and wear were assessed at baseline, 6 months, 1 year, and 2 years using a force gauge and clinical observation, respectively. Prosthetic maintenance, patient satisfaction, and complications were also recorded. Arbitrary retention force values (N) at baseline were set as 20 N for magnet attachments and 25 N for stud attachments. Results: At the end of the 2-year evaluation, retention decreased by 30% in Group A (final mean: 14 N) and 20% in Group B (final mean: 20 N). Group A demonstrated higher wear-related complications (35%) compared to Group B (15%). Patient satisfaction was slightly higher in Group B, with a mean score of 8.5/10 versus 7.8/10 in Group A. Prosthetic maintenance visits were more frequent in Group A (4.5 visits/year) compared to Group B (2.5 visits/year). Conclusion: Stud attachments exhibited superior long-term retention, reduced wear, and greater patient satisfaction compared to magnet attachments in maxillary implant-retained overdentures. Magnet attachments, though less retentive, remain a viable option for patients requiring simplified maintenance and handling.